Determinants of Consumers Attitude in Batik Lampung based on Digital - Wibasuri , Anggalia; Jaya, Indra (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines internet users who adopt the use of digital media in consumers’ attitudes to shop for Batik Lampung with the variable ease of use, perceived usefulness, trust. The purpose of this study was to determine the attitudes of the consents who adopted the use of digital media or one of them the use of e-shopping in Batik Lampung shopping. The samples in this study were as many as 100 customers Batik Lampung were analyzed using structural equation modeling. The results show the Perceived Ease of USe has a negative and insignificant influence on the Attitude to Use variable of Batik Lampung consumers in digital shopping. The perceived benefits have a positive and significant relationship with Attitude to Use Batik Lampung consumers in digital shopping and E-Trust has a positive and significant relationship with the Attitude to Use Batik Lampung consumers in digital shopping.